Revisiting angiomyolipomas: The significance of a rich blood supply on imaging for risk-adapted decision making - David Alonso López Curtis; Alberto Artiles Medina; José Daniel Subiela; Ana Fernández-Mardomingo Díaz; Fernando González Tello; Alfonso Muriel García; Irene de la Parra Sánchez; César Mínguez Ojeda; Miguel Ángel Jiménez Cidre; Victoria Gómez Dos Santos; Francisco Javier Burgos Revilla (Investigative and Clinical Urology)
Purpose: Active surveillance is the preferred management for most renal angiomyolipomas (AMLs) but no risk-adapted follow-up strategy has been established. We aimed to assess the dynamics associated with hemorrhagic complications (HC) and tumor growth (TG) at long-term follow-up of AMLs. Materials and Methods: A single-center retrospective study was conducted, enrolling patients with an AML diagnosed by computed tomography or magnetic resonance imaging. Kaplan–Meier analyses were performed to estimate HC risk and multivariate logistic regression analyses were carried out to evaluate predictors of TG and HC. Results: A total of 150 patients were included. The median follow-up was 64.5 months (interquartile range [IQR] 25–102). Median tumor size at diagnosis was 14 mm (IQR 8–26). During follow-up, 12 patients (8.0%) required selective angioembolization, including 6 in whom the procedure was urgent due to spontaneous bleeding. At 5 years of follow-up, we found a 4.5% risk of HC and 3.6% of patients had a clinically significant growth rate of ≥3 mm/year. The existence of a rich blood supply (odds ratio [OR] 11.10, 95% confidence interval [CI] 1.68–23.54), and the size of AMLs at diagnosis (OR 1.02, 95% CI 1.01–1.04) were predictors for HC. Conclusions: Renal AMLs have a minimal size progression and a very low risk of HC, allowing use of active surveillance as a first-line approach. Imaging features, such as the existence of a rich blood supply, could be useful in identifying patients at higher risk of bleeding for the purpose of risk-adapted decision making.